Annual Plan 1997-98 Volume-III Sector: Transport Andaman And Nicobar Administration - Planning Commission (Planning Commission, 1997)
The port infrastructure have been created under Central Scheme /State Scheme and the requirement of staff for manning the same is to be created during this Plan to have smooth and effective operation. the Container berth No. III & IV is expected to be completed by second quarter of 1996-97 and the requirement of staffs is to be created. This Scheme envisages providing proper infrastructure with trained personnel for the proper reorganization of Port set up in Andaman & Nicobar Islands on the pattern of smaller major ports like Tuticorin and New Mangalore.
Andaman And Nicobar Administration, Planning Department